Functional analysis of developmentally regulated chromatin-hypersensitive domains carrying the alpha 1-fetoprotein gene promoter and the albumin/alpha 1-fetoprotein intergenic enhancer. - Bernier, D (1993)
During liver development, the tandem alpha 1-fetoprotein (AFP)/albumin locus is triggered at the AFP end and then asymmetrically enhanced; this is followed by autonomous repression of the AFP-encoding gene. To understand this regulation better, we characterized the two early developmental stage-specific DNase I-hypersensitive (DH) sites so far identified in rat liver AFP/albumin chromatin: an intergenic DH-enhancer site and the AFP DH-promoter site. Mutation-transfection analyses circumscribed the DH-enhancer domain to a 200-bp DNA segment stringently conserved among species. Targeted mutations, DNA-protein-binding assays, and coexpression experiments pinpointed C/EBP as the major activatory component of the intergenic enhancer. Structure-function relationships at the AFP DH-promoter site defined a discrete glucocorticoid-regulated domain activated cooperatively by HNF1 and a highly specific AFP transcription factor, FTF, which binds to a steroid receptor recognition motif. The HNF1/FTF/DNA complex is deactivated by glucocorticoid receptors or by the ubiquitous factor NF1, which eliminates HNF1 by competition at an overlapping, high-affinity binding site. We propose that the HNF1-NF1 site might serve as a developmental switch to direct autonomous AFP gene repression in late liver development. We also conclude that the intergenic enhancer is driven by C/EBP alpha primarily to fulfill albumin gene activation functions at early developmental stages. Factor FTF seems to be the key regulator of AFP gene-specific functions in carcinoembryonic states.